2020
DOI: 10.1289/ehp7411
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Considerations for Epidemiological Studies of Air Pollution and the SARS and COVID-19 Coronavirus Outbreaks

Abstract: BACKGROUND: Studies have reported that ambient air pollution is associated with an increased risk of developing or dying from coronavirus-2 (COVID-19). Methodological approaches to investigate the health impacts of air pollution on epidemics should differ from those used for chronic diseases, but the methods used in these studies have not been appraised critically. OBJECTIVES: Our study aimed to identify and critique the methodological approaches of studies of air pollution on infections and mortality due to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
139
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(154 citation statements)
references
References 73 publications
3
139
0
2
Order By: Relevance
“…We also could not account for non-residential air-pollution exposure. Spatiotemporal variation in the strains of COVID-19 can introduce bias ( Villeneuve and Goldberg 2020 ), however at the time of publication there was no evidence supporting that strain types can confound the relationship between COVID-19 mortality and air-pollution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We also could not account for non-residential air-pollution exposure. Spatiotemporal variation in the strains of COVID-19 can introduce bias ( Villeneuve and Goldberg 2020 ), however at the time of publication there was no evidence supporting that strain types can confound the relationship between COVID-19 mortality and air-pollution.…”
Section: Discussionmentioning
confidence: 99%
“…While in our analysis the inclusion of area-level prevalence of hypertension, diabetes and COPD did not change the results, the ecological nature of the pre-existing conditions data does not allow us to account for the mediation effect at the individual level. Our study focuses on the mortality after contracting SARS-CoV-2, however we cannot rule out individual susceptibility to becoming infected as an explanation to the uncertainty in the effect estimates ( Villeneuve and Goldberg 2020 ). Such susceptibility can reflect immunosuppression, leading to later increases in inflammation ( Edoardo Conticini et al 2020 ) and thus worse prognosis, or even disease spread, as recent studies have suggested that PM 2.5 can proliferate COVID-19 transmission ( Bianconi et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is currently unknown but probable that the historic fire season, and consequent smoke impacts, has also worsened COVID-related health outcomes, as early evidence suggests that exposure to air pollution increases both COVID cases and deaths in the United States ( 40 , 41 ) (a finding consistent with the relationship between pollution and other viral respiratory illness) ( 42 , 43 ). A better causal understanding of the impact of air pollution on COVID outcomes, including that from wildfires, is a critically urgent research priority, and scholars have provided guidelines on how air pollution/COVID relationships might be best studied ( 44 ). Findings from this research could be important in guiding labor- and finance-constrained firefighting effort and fuels management strategies as the pandemic continues.…”
mentioning
confidence: 99%